Pancreatic cancer is feeling the heat - Elizabeth M Jaffee; Saumya Y Maru (Journal for ImmunoTherapy of Cancer)
Pancreatic adenocarcinoma (PDAC) is considered an immunologically ‘cold’ tumor that fails to attract or support effector T cells. Most PDACs are resistant to immune checkpoint blockade due to the complex signaling pathways that exist within its tumor microenvironment. Recent advances in genomic and proteomic technology advances are finally uncovering the complex inflammatory cellular and intercellular signals that require modulation and reprogramming. The goal is to ‘turn up the heat’ on PDACs with combination immunotherapies that incorporate T cell activating agents and immune modulatory agents, and successfully eradicate tumors. Here, we discuss progress and promising new research that is moving the field toward this goal.